Feasibility and comparability of different platelet function tests in acute stroke with or without prior antiplatelet therapy - Schaefer, Jan Hendrik; Lieschke, Franziska; Urban, Hans; Bohmann, Ferdinand O.; Gatzke, Florian; Miesbach, Wolfgang (Frontiers in Neurology, 2024)
Background The clinical course of ischemic and hemorrhagic strokes can be influenced by the coagulation status of individual patients. The prior use of antiplatelet therapy (APT) such as acetylsalicylic acid (ASA) or P2Y12-antagonists has been inconsistently described as possibly increasing the risk of hemorrhagic transformation or expansion. Since clinical studies describing prior use of antiplatelet medication are overwhelmingly lacking specific functional tests, we aimed to implement testing in routine stroke care. Methods We used fluorescence-activated cell sorting (FACS) with antibodies against CD61 for thrombocyte identification and CD62p or platelet activation complex-1 (PAC-1) to determine platelet activation. Aggregometry and automated platelet functioning analyzer (PFA-200) were employed to test thrombocyte reactivity. FACS and aggregometry samples were stimulated in vitro with arachidonic acid (AA) and adenosine diphosphate (ADP) to measure increase in CD62p-/PAC-1-expression or aggregation, respectively. Results Between February and July 2023, 20 blood samples (n = 11 ischemic strokes; n = 7 hemorrhagic strokes; n = 2 controls) were acquired and analyzed within 24 h of symptom onset. N = 11 patients had taken ASA, n = 8 patients no APT and n = 1 ASA+clopidogrel. ASA intake compared to no APT was associated with lower CD62p expression after stimulation with AA on FACS analysis (median 15.8% [interquartile range IQR 12.6–37.2%] vs. 40.1% [IQR 20.3–56.3%]; p = 0.020), lower platelet aggregation (9.0% [IQR 7.0–12.0%] vs. 88.5% [IQR 11.8–92.0%]; p = 0.015) and longer time to plug formation with PFA-200 (248.0 s [IQR 157.0–297] vs. 121.5 s [IQR 99.8–174.3]; p = 0.027). Significant correlations were noted between AA-induced CD62p expression and aggregometry analysis (n = 18; ρ = 0.714; p < 0.001) as well as a negative correlation between CD62p increase and PFA clot formation time (n = 18; ρ = −0.613; p = 0.007). Sensitivity for ASA intake was highest for PFA (81.8% for values ≥155.5 s). The combination of ASA + clopidogrel also affected ADP-induced CD62p and PAC-1 expression. Conclusion In the clinical setting it is feasible to use differentiated platelet analytics to determine alterations caused by antiplatelet therapy. Among the tests under investigation, PFA-200 showed the highest sensitivity for the intake of ASA in stroke patients. FACS analysis on the other hand might be able to provide a more nuanced approach to altered platelet reactivity.